Zdrowie jako podstawowy potencjał jednostki w osiąganiu sukcesów i samorealizacji oraz zachowania je warunkujące - Obodyńska, Edyta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Health is the paramount. This in itself is the success of the individual, if you can enjoy it. This affects the perceptual quality of life and feasible. On the other hand, health is an essential tool for achieving success in various areas of functioning. Hence the importance of health education place in the family and the school. The content presented here focuses on the issues related to the contemporary, holistic understanding of health as well as some factors that determine them. It also shows, on the basis of existing documents (NPZ, NIPH-NIH), the health situation of the population of the country on the basis of selected health behaviours. In this work attention is drawn to the psychosocial dimension of health, as one of the important determinants of health of the individual, his success and personal happiness.
Keywords: jakość życia; samorealizacja zawodowa; styl życia; umiejętności życiowe; zdrowie; zdrowie psychospołeczne